Probing CH-π(alkyne) interactions in a series of ethynylferrocenes - McAdam, C. John; Cameron, Scott A.; Hanton, Lyall R.; Manning, Anthony R.; Moratti, Stephen C.; Simpson, Jim (CrystEngComm, 2012)
A neoteric correlation between the cyclopentadienyl (Cp)-aryl dihedral angle and crystal packing arrangement is confirmed in the structural determination of three ethynylferrocene substituted naphthalenes. Two of the naphthalenes have approximately orthogonal Cp and aryl ring systems and feature an inversion dimer motif with CH... pi (alkyne) short contacts. This motif is found in other arylethynylferrocenes. DFT calculations suggest the difference in energy between different dihedral conformations is of the same order as a weak hydrogen bond. Focussing on weak hydrogen bonds that involve the ethynyl group, other comparisons are made with a new polymorph of diferrocenylbutadiyne and the trans-isomer of 1,4-diferrocenylbut-1-ene-3-yne. Although the intermolecular forces described for the subject ethynylferrocenes are weak, they nonetheless give rise to distinctive structural motifs that may be exploitable in future supramolecular design.